Reviewing the Verbal Word and Self-Based Word According to Transcendent Theosophy - Mohsen Pirhadi; Ali allah badashti (حکمت اسرا, 2015)
The Mu'tazila and Imamiyah regard the word as limited to the verbal mode and believe that the words of God are the sounds and letters that He makes; they regard the Quran verses as the best signs of God’s speaking. Ash'arites regard the true word as the meanings that are based on the speaker’s self, which has an independent reality and is something different from will and knowledge; they also regard the Quran verses as the best reason for God’s speaking and believe that God’s self-based word in the nature of God is eternal and self-existent. But Mulla Sadra believes that word is the expression of something that implicate the inside of the speaker. According to him, divine word includes all of the beings and God’s actions and God is a speaker in this meaning of the word. He explains the hierarchy of the divine word as follows: the world of divine command, the superior word; the world of soul, the middle word; and the world of institution, the lowest word. Despite the agreement between the Imamiyah, Ash'arites, and Transcendent Theosophy about the verbal word, Mu'tazila regard the word as something limited to verbal word; but Ash'arites and Transcendent Theosophy believe that there is another level for word; however they disagree about the characteristics of this level. In addition to demonstrating the comprehensiveness of the transcendent theosophy, this study has concluded that the utterances of some Quran verses and hadiths is more consistent with the Sadra’s explanation, while the explanations of the other two approaches about the verses concerning the word of God are not established and complete and remain ambiguity in these verses.